Propuesta de mejora en la gestión de la información documentada para la empresa Construcción y Obras Civiles Pinzón S.A.S. (2021)
Document management becomes an important tool for the organization and that allows to manage in an orderly and systemic way the information that is consigned in both physical and digital documents, precisely what the company Construcción y Obras Civiles Pinzón SAS required, therefore, the project focuses on developing an improvement proposal for document management that allows the company to monitor and control all types of documents that are processed both internally and outside the company, and for this, it was necessary to do a diagnosis on the types of documents that are processed in each of the areas of the company, as well as the current times used for the respective processing, once the documents were identified, an analysis of the causes was made that would allow identifying the reasons for the which ones were presenting inefficiencies in document management. The data was analyzed and their purpose was to have at hand different alternatives to manage the management of all the information, seeking to fulfill this need, a Software was developed for the control, management and security of the documented information, unifying and improving the management documentary for the company. The Software facilitates the interaction between all areas of the company in terms of document management.